The Use of Reporting Verbs in Arabic-English Social Science Articles: A Contrastive Corpus-based Analysis - Alasmari, Jawharah Saeed (Journal of Humanities & Social Sciences, 2023)
The division of linguistic verbs into declarative (informational) and performative (constructive) acts is particularly relevant for linguists. Those verbs develop an understanding of how sentences are put together and the numerous ways that ideas can be expressed by using different sentence structures Those verbs develop an understanding of how sentences are put together and the numerous ways that ideas can be expressed by using different sentence structures Information is conveyed through declarative statements, whereas actions and requests are expressed through performative ones. Linguists can better examine language for meaning and function if they have a firm grasp of the distinctions between these two sentence patterns. The use of the verb "suggests" in a sentence like "I recommend that we go out for dinner tonight" indicates that the statement is being made as a suggestion rather than a command. The use of the word "think" in statements like "I think you should do your homework" indicates that the speaker is expressing an opinion rather than stating a fact. Reporting verbs allow speakers to convey their thoughts and feelings more precisely in conversation. As far as I know, computer linguistics research on declarative verbs, notably contrastive analytical studies between Arabic and English, is scarce. Some experts are researching how these two languages are used. One study found that Arabic speakers use more verb phrases than English speakers on the same issue. Also, Arabic prefers non-finite verbs, while English prefers finite verbs. Arabic employs declarative verbs less than English. [1] However, this study examines show Arabic and English academic writers use reporting and informing verbs functionally and positionally in social science texts. A word sketch is used to determine the most common reporting verbs in both languages and compare their usage. The software is used to supply the frequency, which corresponds to the number of occurrences of the verbs in the articles of the two languages. Statistical analysis of reporting verbs can provide a better understanding of which verbs are used most often and in what contexts. Using Hyland’s (2002) paradigm, the results show that reporting verbs in both languages may be classified into research actions, discourse acts, and cognition acts.